¬¬Effect of Soil and Moisture Conservation Technologies on Growth and Grain Yields of Climbing Beans in Lake Mulehe Sub-catchment South-Western Uganda. - Kushaba, Laban Katende (Kabale University, 2024)
The purpose of the study was to examine the effect of soil and moisture conservation technologies on soil properties and crop yield in Lake Mulehe Sub-catchment - Kisoro district, Uganda. The specific objectives of the study were to; (i) identify the common four soil and moisture conservation technologies practiced by farmers in the Lake Mulehe sub-catchment, (ii) determine the effect of the four most practiced soil and moisture conservation technologies practiced by farmers on selected soil physicochemical properties (PH, Organic Matter, Bulk Density, Total Nitrogen and available Phosphorus) in Lake Mulehe sub-catchment and ( iii) determine the effect of the two most used soil and moisture conservation technologies on climbing bean growth and yield in Lake Mulehe sub-catchment. The study employed both descriptive and analytical research designs utilizing mixed methodologies. Sample studies of 100 farmers that were randomly selected were employed to identify the predominant soil and moisture conservation technologies using an observation checklist. Five field typologies were developed based on commonly used soil and moisture conservation technologies i.e. mulch, grass bunds, trenches, terraces, and control (no conservation measure). Soil samples were collected at a depth of 0-15cm from each field, air dried, and analyzed for the selected soil physical and chemical parameters (soil pH, Total nitrogen, organic matter, available phosphorus, and bulk density). Statistical analysis utilized SPSS 20 and Microsoft Excel 2016. The study identified significant adoption rates for soil conservation practices: mulching (20%), grass bunds (17%), stabilized trenches (16%), and terraces (14%). These practices notably influenced soil physicochemical properties with mulching having the most significant impact, with plots exhibiting higher average soil pH (6.46), organic matter (4.65%), phosphorus (15.96 ppm), and lower bulk density (1.06 g/cm3) compared to those with no soil and moisture conservation measures (control plots). Furthermore, mulching showed the highest effectiveness in promoting climbing bean growth and yield, with an average leaf number of 25, plant height of 2.4m, pod number of 84, and grain weight of 61 grams per 100 beans, surpassing both grass bunds and control plots. Given the high adoption of mulching as a soil and moisture conservation technology and its significant benefits in improving soil pH, organic matter, and phosphorus availability, should be widely promoted in the production of climbing beans.